STRATEGI ORANG TUA DALAM MENDIDIK ANAK USIA DINI MENURUT AMSAL 22:6 TERHADAP PERKEMBANGAN KECERDASAN SPIRITUAL ANAK DAN IMPLIKASI BAGI ORANG PERCAYA - Sanjay Nadeak; Eva Sharon (JURNAL TABGHA, 2022)
Spiritual intelligence is one of the important things possessed by early childhood as the nation's successor who is expected to make a positive contribution to the development of the Indonesian nation in the future. Developing spiritual intelligence needs to start from an early age as a foundation for development at the next stage. The research entitled "The Parental Strategy to Educate Early Childhood according to Proverbs 22:6 towards The Spiritual Intelligence Development and Its Implementation At Batam Mandarin Service (Manhop) Indonesian Bethel Church", has a problem formulation of how to develop spiritual intelligence and how the strategy of parents in educating children early age according to Proverbs 22:6. The purpose of this research is to find out how to develop spiritual intelligence of early childhood and how the strategy of parents in educating early childhood according to Proverbs 22:6. This study uses a qualitative method with a literature review and descriptive approach with the process of collecting data through interviews, observations, and documentation of six participants. Based on the results of research and data analysis conducted, it is concluded that the strategy of parents in educating early childhood has an influence on the development of children's spiritual intelligence. In setting a strategy for educating children according to Proverbs 22:6, it takes understanding from parents about the importance of developing spiritual intelligence in early childhood and parental examples in everyday life.